The complete mitochondrial genome of an important medicinal plant, Rehmannia glutinosa (Gaertn.) DC., 1845 (Lamiales, Orobanchaceae) - Yu Bai; Huan An; Rengang Zhang; Yanna Ma; Hongjia Zhang; Zhili Guo; Li Zhao; Zhaoxuan Wang (Mitochondrial DNA. Part B. Resources)
Rehmannia glutinosa, an extensively utilized Chinese herbal medicine, is highly valued for its medicinal properties. In this study, the complete mitochondrial genome (mitogenome) of R. glutinosa was sequenced and assembled for the first time. The mitogenome is 547,032 bp in length, with an overall GC content of 44.97%. The mitogenome contains 67 unique genes, comprising 43 protein-coding, three rRNA, and 21 tRNA genes, with six protein-coding and nine tRNA genes being chloroplast-derived. The phylogenetic analysis, based on the maximum-likelihood criterion, demonstrated that R. glutinosa is closely related to Aeginetia indica and Castilleja paramensis within the family Orobanchaceae.